2021
DOI: 10.1002/eqe.3472
|View full text |Cite
|
Sign up to set email alerts
|

Fatality rates implied by the Italian building code

Abstract: The project Rischio Implicito – Norme Tecniche per le Costruzioni (RINTC) assessed the seismic structural reliability, in terms of the annual rate of earthquakes causing failure, of a large set of code‐conforming buildings, designed to be located in three different sites, representative of low, mid, and high seismic hazard in Italy. It was found that seismic reliability tends to decrease significantly as the site's hazard increases, despite the design actions having the same return period at all sites. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This implies that this point corresponds to a minimum level of seismic safety that the structure will exhibit when designed under any q factor to the right of the demarcation line, since lateral resistance past that point should become insensitive to the reduction of seismic design actions. Thus, although it appears that uniform seismic safety cannot always be achieved between all sites by adjusting the behavior factor, one could acquiesce to q factors that allow structures to exhibit the same risk across high‐hazard sites while remaining below a certain risk threshold at low‐hazard sites, which can be possibly defined as acceptable according to some criterion 44 . However, as already discussed, what constitutes a high‐hazard or a low‐hazard site, in this context, is by no means obvious from the elastic design spectrum alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that this point corresponds to a minimum level of seismic safety that the structure will exhibit when designed under any q factor to the right of the demarcation line, since lateral resistance past that point should become insensitive to the reduction of seismic design actions. Thus, although it appears that uniform seismic safety cannot always be achieved between all sites by adjusting the behavior factor, one could acquiesce to q factors that allow structures to exhibit the same risk across high‐hazard sites while remaining below a certain risk threshold at low‐hazard sites, which can be possibly defined as acceptable according to some criterion 44 . However, as already discussed, what constitutes a high‐hazard or a low‐hazard site, in this context, is by no means obvious from the elastic design spectrum alone.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, although it appears that uniform seismic safety cannot always be achieved between all sites by adjusting the behavior factor, one could acquiesce to q factors that allow structures to exhibit the same risk across high-hazard sites while remaining below a certain risk threshold at low-hazard sites, which can be possibly defined as acceptable according to some criterion. 44 However, as already discussed, what constitutes a high-hazard or a low-hazard site, in this context, is by no means obvious from the elastic design spectrum alone.…”
Section: [-] [G] [-] [-] [G] [-] [-] [G] [-] [-] [G] [-]mentioning
confidence: 94%
“…showed that designing structures based on uniform hazard does not result in structures with uniform risk, and introduced risk‐targeted seismic design maps. The nonuniform risk for structures designed by seismic code was recently confirmed for Italy 17 . A risk‐targeted approach was followed by Douglas et al 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The nonuniform risk for structures designed by seismic code was recently confirmed for Italy. 17 A risk-targeted approach was followed by Douglas et al 18 and Silva et al, 19 who developed risk-targeted design maps for mainland France and Europe, respectively, but Japan remained conservative regarding risk-based seismic hazards due to reasons recently discussed by Suzuki et al 20 In parallel, many variants of seismic design procedures based on risk metrics were introduced. Franchin and Pinto 21 presented a method for seismic design of reinforced concrete structures to meet performance requirements expressed in terms of risk.…”
Section: Introductionmentioning
confidence: 99%